2020
DOI: 10.1038/s41598-020-57776-3
|View full text |Cite
|
Sign up to set email alerts
|

The antibiotic vancomycin induces complexation and aggregation of gastrointestinal and submaxillary mucins

Abstract: Vancomycin, a branched tricyclic glycosylated peptide antibiotic, is a last-line defence against serious infections caused by staphylococci, enterococci and other Gram-positive bacteria. Orally-administered vancomycin is the drug of choice to treat pseudomembranous enterocolitis in the gastrointestinal tract. However, the risk of vancomycin-resistant enterococcal infection or colonization is significantly associated with oral vancomycin. Using the powerful matrix-free assay of co-sedimentation analytical ultra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 85 publications
(99 reference statements)
0
27
0
Order By: Relevance
“…The model for the normal renal function group included SCR as a covariate, but the model for the ARC group did not. Since vancomycin is hydrophilic with a large molecular volume and many non-ionic groups ( 22 ), the tissue distribution speed of vancomycin is expected to be limited by the lipid membrane. Moreover, Du et al, by using an established physiologically based pharmacokinetics (PBPK) model, found out that the concentration of vancomycin in renal tubules was about 40–50 times higher than that in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…The model for the normal renal function group included SCR as a covariate, but the model for the ARC group did not. Since vancomycin is hydrophilic with a large molecular volume and many non-ionic groups ( 22 ), the tissue distribution speed of vancomycin is expected to be limited by the lipid membrane. Moreover, Du et al, by using an established physiologically based pharmacokinetics (PBPK) model, found out that the concentration of vancomycin in renal tubules was about 40–50 times higher than that in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Most human or animal airborne pathogens will be contained in aerosol droplets consisting of principally aqueous fluid, glycoproteins, and mucins. Mucin has been shown to dissolve in phosphate buffered saline solution or PBS [27]. However, phosphate buffers used in electrospray can accumulate on the spray tip owing to their nonvolatility and clog over time.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic vancomycin is normally administered intravenously but can also be administered orally to treat bacterial based gasterointestinal diseases such as pseudomembranous enterocolitis. One of the issues however that are peculiar to oral administration is the possible complications through potential interactions with gasterointestinal mucus and in particular the mucin glycoprotein component: A study involving analytical ultracentrifugation reinforced by quasi-elastic or “dynamic” light scattering (DLS) and environmental scanning electron microscopy (ESEM) was therefore undertaken to explore for the presence of interactions which could help explain the poor absorption of the antibiotic from the intestine and the glycopeptide impacts on the intestinal microbiota and its connection with antimicrobial resistance [ 25 ]. A somewhat different AUC approach to probe these large supramolecular aggregation reactions rather than the study of the well-defined dimerisation (vancomycin by itself) or dimerisation/tetramerisation (band 3) described above, was taken.…”
Section: Vancomycin-mucin Interactionsmentioning
confidence: 99%
“…We will also consider some of the studies done so far on the enterococcal kinase VanS system under aqueous only conditions together with the interactions involving the ligand vancomycin. Relevant to oral-based formulations we will also consider how the analytical ultracentrifuge has revealed strong interactions between vancomycin and mucin [ 25 ]. To avoid the review becoming opaque to the non-specialist without a background in hydrodynamics, a minimum of methodological detail is given, but key follow-up references are provided instead.…”
Section: Introductionmentioning
confidence: 99%